2020
DOI: 10.32598/ijt.14.3.626.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Zinc Oxide Nanoparticles Exposure Produces Hepatic and Pancreatic Impairment in Female Rats

Abstract: Background: Zinc Oxide (ZnO) nanoparticles are used for various industrial and domestic purposes and its release into the environment leads to the adverse effects among humans. This study aimed to evaluate the effect of rat exposure to ZnO nanoparticles on the histopathology of the liver and pancreas tissues, and serum oxidative stress parameters. Methods: Eighty female adult Wistar rats were divided into eight experimental, control and sham groups. They received ZnO nanoparticles at 4, 8, 25, 50, 100, or 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
4
4
0
Order By: Relevance
“…This decrease in the % b.wt after CZF NPs injection indicates that this complex could have a toxic effect on the body organs. This nding was in accordance with the previous study that showed % b.wt changes was decreased upon the injection of mice with ZNO NPs (Novotna et al 2016;Hosseini et al 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This decrease in the % b.wt after CZF NPs injection indicates that this complex could have a toxic effect on the body organs. This nding was in accordance with the previous study that showed % b.wt changes was decreased upon the injection of mice with ZNO NPs (Novotna et al 2016;Hosseini et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the evidence of histopathological lesions, hyperemia, in ammatory cell in ltration, and necrosis were noted in the liver and pancreas tissue slides upon microscopic examinations. Finally, the body and liver weights decreased in the rat groups receiving ZnO nanoparticle dose dependently (Hosseini et al 2020).…”
Section: Introductionmentioning
confidence: 90%
“…This discovery might be a result of hypertension and the harmful effects of ZnO-NPs on the epithelial layer that lines blood vessels, which in turn causes inflammation in the liver. These findings corroborated those of previous research by Hosseini et al [ 24 ] that examined the effects of injecting ZnO-NPs into the peritoneum of adult female mice over the course of 30 days at progressively higher doses (4, 8, 25, 50, 100, and 200 mg/kg). Liver necrosis, inflammatory cell infiltration, and blood vessel congestion were the results.…”
Section: Discussionsupporting
confidence: 91%
“…ZnO‐NPs offer antibacterial, anticarcinogenic, wound‐healing, anti‐inflammatory, and antiapoptotic capabilities for use in medical applications (Agarwal et al, 2017). In fact, because of their small diameters (100 nm), NPs can enter the body, pass through biological barriers like the placenta, blood–brain barrier, and alveoli, and accumulate in specific organs, resulting in several biochemical and physiological disturbances (Hosseini et al, 2020; Yousef et al, 2019). In rats, ZnO‐NPs can impair neuronal systems in the brain and impair learning and memory (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%